Demineralization of Sargassum spp. Macroalgae Biomass: Selective Hydrothermal Liquefaction Process for Bio-Oil Production - Díaz-Vázquez, Liz M.; Rojas-Pérez, Arnulfo; Fuentes-Caraballo, Mariela; Robles, Isis V.; Jena, Umakanta; Das, K. C. (Frontiers in Energy Research, 2015)
Algae biomasses are considered a viable option for the production of biofuel because of their high yields of oil produced per dry weight. Brown macroalgae Sargassum spp. are one of the most abundant species of algae in the shores of Puerto Rico. Its availability in large quantity presents a great opportunity for use as a source of renewable energy. However, high ash content of macroalgae affects the conversion processes and the quality of resulting fuel products. This research studied the effect of different demineralization treatments of Sargassum spp. biomass, subsequent hydrothermal liquefaction (HTL) and bio-oil characterization. Demineralization constituted five different treatments: nanopure water, nitric acid, citric acid, sulfuric acid, and acetic acid. Performance of demineralization was evaluated by analyzing both demineralized biomass and HTL products by the following analyses: total carbohydrates, proteins, lipids, ash content, caloric content, metals analysis, Fourier Transform Infrared - Attenuated Total Reflectance (FTIR-ATR) Spectroscopy, Energy Dispersive Spectroscopy (EDS), Scanning Electron Microscopy (SEM), and GCMS analysis. HTL of Sargassum spp. before and after citric acid treatment, was performed in a 1.8 L batch reactor system at 350°C with a holding time of 60 min and high pressures (5-21 MPa). Demineralization treatment with nitric acid was found the most effective in reducing the ash content of the macroalgae biomass from 27.46% to 0.99% followed by citric acid treatment that could reduce the ash content to 7%. Citric acid did not show significant leaching of organic components such as carbohydrates and proteins, and represented a less toxic and hazardous option for demineralization. HTL of untreated and citric acid treated Sargassum spp. resulted in bio-oil yields of 18.4±0.1 % and 22.2±0.1 % (ash free dry basis), respectively.